Calvinize : signature techniques of Photoshop artist Calvin Hollywood - Hollywood, Calvin (Peachpit Press, 2010)
Calvin Hollywood is a photo artist from Heidelberg, Germany who combines photography and image editing in a most imaginative way. His personal style is characterized by the hyper sharpness, high contrasts, and almost painted look of his photos (http://www.calvinhollywood-blog.com/portfolio/). Digital editing plays an important role in his photographic work, but Hollywood emphasizes getting the shot right from the start. He considers lighting very important, but the surroundings and the model's styling are also key and he always tries to factor textures and details into the shot. This photo collection contains more than 100 of Calvin Hollywood's most spectacular pictures as well as his thoughts on topics such as Photoshop, plug-ins, outfits, lighting, planning, time management, and more. The book also comes with over four hours of video tutorials created and produced by Video2Brain, creators of the popular Learn By Video series. In the videos, Hollywood walks viewers step-by-step through his signature techniques and shows readers exactly how he used them to create many of the images featured in the book.